Penerapan respiratory fit test pada kader tuberkulosis dalam pencegahan penularan tuberkulosis di Palembang - Pasaribu, Rouly; Fathurrachman, Alif; Wirdah, Aisyah; Andriani, Linda; Sudarto, Sudarto; Rasyid, Ahmad; Ahmad, Zen (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
According to the 2023 world tuberculosis (TB) report, Indonesia ranks 2nd in the world with an estimated 1,060,000 cases. Transmission of TB germs through droplets that enter the airways. TB cadres play an important role in assisting TB patients undergoing treatment, especially drug-resistant TB. TB cadres also play a role in providing health information to TB patients to achieve optimal treatment and achieve treatment success. During their roles, TB cadres who are in contact with active pulmonary TB patients are very vulnerable to infection. The implementation of respiratory fit tests for TB cadres in Palembang is needed, so that TB cadres in Palembang do not contract TB germs. Through the TB cadre organization, namely the Sriwijaya Healthy Society, 15 TB cadres were given counseling on the proper use of respirators and in accordance with conducting a fit test first. Through individual simulations with respirator fit tests, appropriate application was obtained for all TB cadres in using appropriate respirators. Through this activity, it is hoped that TB cadres in the city of Palembang will be able to carry out their duties safely and comfortably.